COVID -19–Associated Acute Necrotizing Encephalopathy: A Case Report - Fazelnia, Faezeh; Hasani, sahar; Zamani, fatemeh; Shabanian, Reza (Iranian Journal of Child Neurology, 2023)
Abstract COVID-19 is a pandemic disease in which most patients have pulmonary symptoms. However, several cases of CNS involvement associated with COVID-19 have been reported. Acute necrotizing encephalopathy of childhood (ANEC) is a rare CNS complication of viral infections such as influenza, herpes virus, and COVID-19, leading to high mortality and morbidity rates. Several cases of COVID-19-associated acute necrotizing encephalopathy (ANE) have been reported since March 2020 in adults, with just a few cases in pediatrics. This article reports a 5-month-old child who presented with seizures, with the final diagnosis of ANE as a complication of COVID-19. MRI findings of ANEC, as reported in most COVID-19-associated ANEC case reports, involve bilateral, symmetric, multifocal lesions in the central thalami. Moreover, the brainstem, cerebral white matter, and cerebellum could be affected. The prognosis of COVID-19-associated ANE is poor, leading to neurologic dysfunction or mortality. COVID-19-associated ANE cases must be reported, especially in pediatrics, with detailed clinical history, laboratory data, and radiologic findings to introduce diagnostic criteria, prognosis, and a management protocol.